2023
DOI: 10.1038/s41467-023-41729-1
|View full text |Cite
|
Sign up to set email alerts
|

A digital twin for DNA data storage based on comprehensive quantification of errors and biases

Andreas L. Gimpel,
Wendelin J. Stark,
Reinhard Heckel
et al.

Abstract: Archiving data in synthetic DNA offers unprecedented storage density and longevity. Handling and storage introduce errors and biases into DNA-based storage systems, necessitating the use of Error Correction Coding (ECC) which comes at the cost of added redundancy. However, insufficient data on these errors and biases, as well as a lack of modeling tools, limit data-driven ECC development and experimental design. In this study, we present a comprehensive characterisation of the error sources and biases present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 46 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…These error rates are in-line with the analysis by the original authors, 11,12 and in stark contrast to the error rates commonly observed for established commercial DNA synthesis, which usually lie below 0.02 nt -1 even in the worst case. 9,18 Interestingly, deletion errors dominate both in photolithographic and commercial DNA synthesis. 9,18,21 However, similarly to electrochemical synthesis in which a failure to deprotect the growing oligo causes a deletion, 22,23 part of the high error rates during photolithographic synthesis could be attributed to insufficient deprotection during the illumination step.…”
Section: Photolithographic Synthesis Yields Highly Erroneous Dnamentioning
confidence: 99%
See 4 more Smart Citations
“…These error rates are in-line with the analysis by the original authors, 11,12 and in stark contrast to the error rates commonly observed for established commercial DNA synthesis, which usually lie below 0.02 nt -1 even in the worst case. 9,18 Interestingly, deletion errors dominate both in photolithographic and commercial DNA synthesis. 9,18,21 However, similarly to electrochemical synthesis in which a failure to deprotect the growing oligo causes a deletion, 22,23 part of the high error rates during photolithographic synthesis could be attributed to insufficient deprotection during the illumination step.…”
Section: Photolithographic Synthesis Yields Highly Erroneous Dnamentioning
confidence: 99%
“…9,18 Interestingly, deletion errors dominate both in photolithographic and commercial DNA synthesis. 9,18,21 However, similarly to electrochemical synthesis in which a failure to deprotect the growing oligo causes a deletion, 22,23 part of the high error rates during photolithographic synthesis could be attributed to insufficient deprotection during the illumination step. The two aforementioned high-density syntheses by Antkowiak et al 12 did not show the same error distribution, as substitution errors were dominating instead (see File 2 and File 3 in Fig.…”
Section: Photolithographic Synthesis Yields Highly Erroneous Dnamentioning
confidence: 99%
See 3 more Smart Citations